Neuropsychological assessment of Spanish-speaking populations: translations and norms for three tests - Cummings, Thomas A., author; Deffenbacher, Jerry L., advisor; Chavez, Ernest L., advisor (Colorado State University. Libraries, 2000)
Increasing demand for neuropsychological assessment of the growing population of Spanish-speakers in the United States has necessitated the development of culturally appropriate measures of cognitive functioning. Previously, the use of literal translations, untrained interpreters, and English-speaking norms has resulted in culturally-biased and unreliable evaluations. The present study addresses the lack of appropriate measures by developing culturally-relevant translations of a word list memory task, a test of visuoconstruction, and a test of non-verbal reasoning. Normative data on a sample of 148 Spanish-speaking participants stratified by age and education are provided. Current results reveal age effects on both memory and nonverbal measures. Generally, performance declines with increasing age. There were no effects of education on the memory measures. Education effects were present on the nonverbal measures; performance improved with higher levels of education. No effects of gender, occupation, or acculturation were found on any of the measures. For the validation of these measures further research is needed involving clinical populations and expanded normative data collection.
Keywords: psychotherapy; psychological tests; quantitative psychology; clinical psychology